PREVALENCE OF NON-COMPLIANCE OF ROUTINE BLOOD GLUCOSE MONITORING IN UNCONTROLLED TYPE 2 DIABETICS PRESENTING AT A TERTIARY CARE HOSPITAL.: J Peop Univ Med Health Sci. 2025:15(3), 44-54. http://doi.org/10.46536/jpumhs/2025/15.03.657 - Qadeer Muhammad Khan1, Naseer Ahmad2, Muhammad Sami3, Izhar Ul Haq4, Fazal Rabi5, Sana6. , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: An important part of managing type 2 diabetes mellitus (T2DM) is self monitoring of blood glucose (SMBG). The current study aimed to evaluate the frequency of routine SMBG non-compliance in patients with uncontrolled type 2 diabetes. METHODS: This cross sectional study was carried out from July to December 2024 at the Hayatabad Medical Complex's Department of Diabetes & Endocrinology in Peshawar. 294 individuals with uncontrolled type 2 diabetes were included in the study. Based on adherence to the SMBG, participants were divided into groups that were compliant and those that were not. Structured questionnaires and medical records were used to gather information on demographics, disease features, SMBG practices, and clinical outcomes (diabetes ketoacidosis, hypoglycemia, neuropathy, retinopathy, and nephropathy). SPSS version 26.0 was used for the statistical analysis. RESULTS: Of 294 participants, 171 (58.2%) were non-compliant with SMBG. Non-compliance was significantly associated with higher incidence of diabetic ketoacidosis (p = 0.002), severe hypoglycemia (p = 0.004), neuropathy (p = 0.003), retinopathy (p = 0.001), and nephropathy (p < 0.001). Lower education level and income were also significantly linked to non-compliance (p < 0.001). CONCLUSION: Non-compliance with routine SMBG is prevalent among uncontrolled T2DM patients and is associated with significantly higher rates of acute and chronic complications. Targeted educational and economic interventions are urgently needed.